Biophysiological measures: A critique on MS theses in Shaheed Beheshti Faculty of Nursing and Midwifery - Darvishpoor Kakhaki, A; Yaghmaei, F; Mozafary, M (Advances in Nursing & Midwifery, 2008)
Background Biophysiological measures are the most common instruments for collecting data in medical science studies. To collect valid and reliable data, it is critical to apply these measures appropriately. Purpose The aim of this study was to assess and critique the validity and reliability of biophysiological measures in MS theses in Shaheed Beheshti Faculty of nursing and midwifery. Methods 343 nursing and 166 midwifery theses were first assessed to identify those with biophysiological measures and in 48 ones with these measures, methods used for identifying their validity and reliability were checked. Results Findings showed that scientific methods for examining accuracy, selectivity, precision, sensitivity and calibration of biophysiological measures were not accurately applied. Conclusion This study reveals inadequate application of scientific methods regarding to accuracy and precision of biophysiological measures. Accordingly, better methods for identifying accuracy and precision of biophysiological measures should be applied. Keywords Biophysiological measures, Nursing thesis, Midwifery thesis.